Analysis of Internal Audit, Whistleblowing System and Organizational Culture in Fraud Prevention (A Case Study of PT Pos Indonesia) - Ninzi Maiviza, Dwita; Rusmawan Kusumah, Wedi (DINASTI RESEARCH, 2025)
This study is driven by the high risk of fraud that can harm State-Owned Enterprises (SOEs), including PT Pos Indonesia, thus necessitating effective prevention efforts through the strengthening of internal audit, the whistleblowing system, and organizational culture. The purpose of this research is to analyze the role of these three factors in preventing fraud within the company. This study employs a qualitative approach using a case study method, with data collected through in-depth interviews with several informants who have insight into the company's control systems and corporate governance. The results show that internal audit has actively contributed by identifying areas vulnerable to fraud and providing appropriate corrective recommendations. The whistleblowing system is formally established, yet its effectiveness still requires improvement through better protection for whistleblowers and clear follow-up on reports. The organizational culture, grounded in AKHLAK values, also proves to enhance employee integrity and create a work environment that discourages fraudulent behavior. In conclusion, these three elements complement one another and significantly contribute to building an effective fraud prevention system at PT Pos Indonesia, offering important implications for strengthening internal control within the public sector.